EFFECT OF THREE MINUTE STEP TEST ON COGNITION AMONG MEDICAL STUDENTS - Manadhar, Srista; Chettri, Sunit; Rajbhandari Pandey, Karishma; Limbu, Nirmala; Baral, Dharanidhar; Raj Pandey, Dipesh (MNJ (Malang Neurology Journal), 2021)
Background: Regular physical exercise is linked to produce beneficial influence on cognitive functions. Cognition can be evaluated by Stroop test where a person's selective attention capacity, skills and processing speed are assessed. Limited work has been done to explore the acute effect of exercise on cognition. Objective: To assess whether acute exposure to submaximal aerobic exercise of three minutes can bring changes in the cognitive function (selective attention and cognitive processing ability). The secondary objective was to assess the physical fitness index of medical students.Methods: Twenty  four apparently  healthy third year male medical students of BPKIHS (B. P. Koirala Institute of Health Sciences) having  mean  age  of  22.33 ± 1.09 years, body height and weight of 170.10 ± 5.85 cm of 65.38 ± 8.84 kg respectively were recruited. A computer based online version of Stroop Test was done to identify cognitive performance in resting sitting position. Then participants were asked to perform 3 min step test. A recovery time of 5 min was given post exercise and Stroop Test was assessed again. Statistical analysis was done using Paired T test. Data are expressed in mean and SD. Level of significance is considered at p<0.05.Results: The reaction time to Stroop Test was significantly reduced after acute physical exercise (before exercise (43.37 ± 7.7s) vs after exercise (36.14 ± 3.6s), p = 0.001). However, no significant difference in the number of correct response to Stroop Test before (19.71 ± 1.08) and after (19.79 ± 0.51) the acute exercise (p=0.575) was observed.Conclusion: Acute bout of aerobic physical exercise improves attention and execution aspects of cognitive function as measured by Stroop Test in young medical students.